Molecular‐Layer‐Deposited Zincone Films Induce the Formation of LiF‐Rich Interphase for Lithium Metal Anodes. Issue 12 (31st January 2023) - Chang, Shaozhong; Fang, Jiabin; Liu, Kai; Shen, Zihan; Zhu, Lin; Jin, Xin; Zhang, Xuejin; Hu, Chaoquan; Zhang, Huigang; Li, Ai‐dong
Abstract: Lithium metal anodes suffer from low Coulombic efficiency and dendritic growth owing to an unstable solid electrolyte interphase (SEI), which limit the practical applications of lithium metal anodes. Here, zincone (ZnHQ) is conformally fabricated on 3D copper nanowires (CuNWs) via a molecular layer deposition (MLD) technology. Upon polarization, the terminal oxygen of ZnHQ serves as a strong nucleophilic agent to attack Li bis (trifluoromethanesulfonyl)imide, yielding a LiF‐rich SEI. This SEI facilitates the Li transport, shuts off the electron conduction, and inhibits the growth of lithium dendrites. In addition, the zinc atoms of ZnHQ induce favorable Li deposition owing to their lithiophilicity. These advantages enabled by MLD make the ZnHQ‐modified CuNW (CuNW@ZnHQ) an ideal Li metal anode, which demonstrates excellent cyclability. A symmetrical cell of CuNW@ZnHQ shows high cycling stability for more than 7000 h at the current density of 1 mA cm −2 . When pairing with a Ni/Co/Mn ternary oxide cathode (NCM523), the resultant CuNW@ZnHQ||NCM full cell is cycled for 1000 cycles with a 90% capacity retention at an areal capacity of 3.2 mAh cm −2 . The MLD technology brings new opportunities for next‐generation high‐energy Li metal batteries. Abstract : A polar and lithiophilic zincone is fabricated on 3D copper nanowires by a molecular layer deposition technique. Because of the formation of LiF‐rich interphase and the lithiophilicity of zinc, the resultant CuNW@ZnHQ electrode realizes high cycling stability for more than 7000 h at 1 mAh cm −2 .